UPAYA PENCEGAHAN DEGRADASI MORAL REMAJA YANG MENGARAH PADA PERNIKAHAN DINI MELALUI KAJIAN SUTTA PITAKA - Dhita Indah Hapsari; Kuntari Hanggini Sutanto; Evi Ratnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to examine efforts to prevent moral degradation that leads to early marriage through the study of Sutta Pitaka. The methodology used in this research is a qualitative methodology with a literature study approach or what is often also known as library research to obtain information data by placing data facilities in libraries such as books, documents, magazines, records of historical stories or pure library research related to the object of research then compiled in a description without being exaggerated or reduced until finally making a conclusion from the research that has been carried out. The results of this study indicate that 1) Moral degradation and early marriage among teenagers can be prevented by implementing moral teachings in Buddhism, such as those contained in the Samajīvī Sutta and Maṅgala Sutta. 2) The teachings in the sutta pitaka provide important guidance in choosing healthy relationships, making wise decisions, and maintaining morality and personal integrity 3) By understanding and practicing the teachings in the sutta pitaka, teenagers are expected to avoid early marriage and maintain their moral quality, so as to build a better and harmonious life. 4) Understanding the effects of early marriage.